Modelo regulatório híbrido da educação superior privada: possibilidades, limites e desafios - Corrêa, Eneida Cardoso de Britto (2015)
Over the last twenty years, we have noticed the entry of profit-seeking private entities into the higher education field, motivated and induced by decisions on education policies aiming at the ideal of access to education combined with social inclusion. Therefore, private institutions established a new model of Higher Education focusing on Market, creating opportunities for the segment to grow outside of an economic regulatory procedure. Currently, the possibilities of approaching for regulation on economic sectors have been expanded, also on formats that aren’t necessarily the standard for autonomous agencies, making it possible for there to be entities which are similar to regulatory agencies, and therefore possessing regulatory function, such as the Ministry of Education and its supervised regional authorities. The so called qualitative social regulation - the offer of positions and authorization of courses - proves to be insufficient to arrange and articulate agents’ actions, in a regulatory environment of increasing social and economic complexity. The hybrid regulatory model of private schools suggests articulating/combining the well established yardsticks for social regulation with the principles of economic regulation, in a new form of regulatory approach which gathers the following dimensions: economic fundaments; implementation of public policies divided by sector, region and purpose; institutional planning that prioritizes new guidelines to the entry and maintenance on the Federal System of Education - authorizations and registrations; supervision and control; prospection, evaluation, and accountability - and access of higher education institutions to programmatic public policies, of general character, assuring public interest, effectiveness, quality, competitiveness and the social value on Private Higher Education. Key-words: private higher education; social and economic regulation; Market; Third sector; hybrid regulatory model.